Electrodeposition of graphene by cyclic voltammetry on nickel electrodes for microbial fuel cells applications. (7th January 2019) - Zhu, Weihuang; Gao, Haoxiang; Zheng, Fei; Huang, Tinglin; Wu, Fengchang; Wang, Huan
Summary: Ni electrode was modified with graphene by the electrodeposition (ED) method to prepare an anode (anode‐ED) for microbial fuel cell (MFC). Electrochemical and morphological characterizations of anode‐ED along with the effects of anode modification on the MFC performance were investigated. The graphene modification based on cyclic voltammetric electrodeposition resulted in the decrease of charge transfer resistance ( R ct ) and improved extracellular electron transfer efficiency of anode. The maximum power density obtained from the MFC equipped with anode‐ED was 25.83 and 17.86 times larger than those of MFCs equipped with bare Ni anode and anode modified with graphene by traditional hydrothermal treatment method (anode‐HT), respectively. The electrochemical impedance spectroscopy (EIS) analysis results indicated that the R ct of anode decreased significantly after inoculation during the MFC operation. The improvement in power density was attributed to the decreasing R ct and the biocompatibility of graphene modified on anode‐ED surface. This study presented an effective electrodeposition method to make graphene‐modified anodes, which could improve the MFC performance. Abstract : Graphene was electrodeposited on Ni surface to prepare anodes for MFC. Charge transfer resistance of graphene‐modified anodes (anodes‐ED) significantly decreased and anodes‐ED showed electrocatalytic activity. Electrodeposited graphene on anode significantly enhanced the performance of MFC.